2021
DOI: 10.3389/fphys.2021.780206
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Regulation of the Large-Conductance, Calcium and Voltage-Activated Potassium Channel, BK

Abstract: Hypoxia is a condition characterized by a reduction of cellular oxygen levels derived from alterations in oxygen balance. Hypoxic events trigger changes in cell-signaling cascades, oxidative stress, activation of pro-inflammatory molecules, and growth factors, influencing the activity of various ion channel families and leading to diverse cardiovascular diseases such as myocardial infarction, ischemic stroke, and hypertension. The large-conductance, calcium and voltage-activated potassium channel (BK) has a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 178 publications
(281 reference statements)
0
13
0
Order By: Relevance
“…30–43 Of these 13 hypoxia-related genes, 10 shared a connection to the well-known HIF (hypoxia-inducible factor) pathway (Apln, Egln3, Eif4ebp1, Fmo2, Gnmt, Lrrc55, Mycn, Nqo1, Nt5e, and P4ha1). 30–33,35,36,38–40,42 A subset of these HIF-related transcripts are illustrated in Figure 5B.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…30–43 Of these 13 hypoxia-related genes, 10 shared a connection to the well-known HIF (hypoxia-inducible factor) pathway (Apln, Egln3, Eif4ebp1, Fmo2, Gnmt, Lrrc55, Mycn, Nqo1, Nt5e, and P4ha1). 30–33,35,36,38–40,42 A subset of these HIF-related transcripts are illustrated in Figure 5B.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43] Of these 13 hypoxiarelated genes, 10 shared a connection to the well-known HIF (hypoxia-inducible factor) pathway (Apln, Egln3, Eif4ebp1, Fmo2, Gnmt, Lrrc55, Mycn, Nqo1, Nt5e, and P4ha1). [30][31][32][33]35,36,[38][39][40]42 A subset of these HIF-related transcripts are illustrated in Figure 5B. RBM3 and CIRP have known roles in physiologic stress response.…”
Section: Ckd Mice Die From Bradyarrhythmias Progressing To Asystolementioning
confidence: 99%
See 2 more Smart Citations
“…Our group recently showed that HIF-2α is involved in preventing internalization and degradation of surface expression of epithelial Na channels (ENaC) in primary alveolar epithelial cells exposed to in vitro hypoxia, and it improved the amiloride-sensitive alveolar fluid reabsorption, which was decreased in in vivo hypoxia [89]. Ochoa et al recently reviewed the regulation of the calcium and voltage-activated potassium channel (BK) by hypoxia, HIF-1α and its relation with CVD [90]. Most of these studies have been performed in vitro; thus, whether similar regulations by HIFs also occur in vivo still needs to be identified.…”
Section: Hif-1α In Regulating Nka In the Ischemic Heartmentioning
confidence: 99%